A polyethylene glycol functionalized hyaluronic acid coating for cardiovascular catheter lubrication. (November 2020) - Wan, Hongping; Lin, Chengxiong; Kaper, Hans J.; Sharma, Prashant K.
Abstract: Catheterization is a common medical operation for cardiovascular disease diagnosis and treatment, where low friction is attained through hydrophilic lubricious coatings. But these coatings can cause iatrogenic complications when particles become lose and float freely in the blood stream. Here we present an ultra-thin coating based on polyethylene glycol (PEG) functionalized hyaluronic acid (HA). The mussel-inspired biopolymer hyaluronic acid was first conjugated to dopamine (DN) to get HADN and then poly (ethylene glycol) bis (3-amino-propyl) terminated (PBA) was used to functionalize the HADN with PEG. The reciprocating sliding ball-on-flat ex vivo model based on PU ball and porcine aorta was used to evaluate the lubrication performance and the results suggest coating of HADN with best lubrication enhancement. After 40 min friction test, the surface of aorta remained intact for HADN-PBA coated PU as compared to HADN coating and positive control (sliding against bare PU). The amount of glycocalyx, number of endothelial nuclei and intima surface of aorta for coated PU were similar to negative control (without rubbing). Besides lubrication, the high biocompatibility suggests the coating of HADN-PBA is safe and lubrication benefits to the cardiovascular catheter. Graphical abstract: Unlabelled Image Highlights: The catheter-blood vessel sliding interface was successfully mimicked using a reciprocating aorta- PU (polyurethane) ballfrictional system. An ultra-thin, lubricant, and biocompatible coating based on two biopolymers was successfully fabricated. The coating significantly improved the lubrication of polyurethane and prevented the wear of blood vessel. The HADN-PBA thus is a strong candidate for cardiovascular catheter coating.